ANALYSIS OF FORMALDEHYDE PRESERVATIVES IN WET ANCHOVY (Stolephorus Sp.) FROM TRADITIONAL MARKETS IN MAKASSAR CITY, SOUTH SULAWESI - Adriani, Adriani; Karim, Abdul; dali, seniwati (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2019)
Food preservatives are very important ingredients in improving the quality and production of processed foods. However there are various presenvatives and such preservatives such as formaldehide are not allowed. This study aims to determine the content of preservatives in fresh anchovy (stolephorus sp.) from the traditional market of Makassar City South Sulawesi. Formaldehyde preservatives is identified by qualitative and quantitative test, qualitative formaldehyde was tested using Schryver reagent using UV-Vis Spectrophotometer analysis method. The result of qualitative analysis showed that all samples contained formaldehyde, with the concentration value of 0.2702ppm; 0.1307ppm; 0.0871ppm in Daya Market A; Daya Market B; Daya Market C samples, respectively. The content of 0.1612ppm; 0.2223ppm; 0,1525ppm in Antang Market A; Antang Market B; Antang Market C samples, respectively. The content of 0,1918ppm;0,0087ppm; 0.2877ppm in Terong Market A; Terong Market B; Terong Market C, samples, respectively and the content of 0.1394ppm; 0.1961ppm; 0,0043, in Pa’baeng-baeng Market A; Pa’baeng-baeng Market B; Pa’baeng-baeng Market C samples, respectively. The lowest formaldehyde level was found in Terong Market C with level of 0.0087ppm and the highest formaldehyde level was in Pa’baeng-baeng Market C with the level of 0.2877ppm.